Effect of maternal immunisation with multivalent vaccines containing inactivated poliovirus vaccine (IPV) on infant IPV immune response: A phase 4, multi-centre randomised trial. Issue 7 (10th February 2023) - Grassly, Nicholas C; Andrews, Nick; Cooper, Gillian; Stephens, Laura; Waight, Pauline; Jones, Christine E; Heath, Paul T; Calvert, Anna; Southern, Jo; Martin, Javier; Miller, Elizabeth
Highlights: In the UK, vaccination of pregnant women with DTaP/IPV generates high levels of maternally-derived antibodies in the infant and protects against severe disease including infant pertussis. These antibodies have the potential to interfere with responses in the infant to their primary immunisation series when given early in life. We found significantly lower seroconversion following immunisation with inactivated poliovirus vaccine (IPV) at 2, 3 and 4 months of age in infants born to mothers given a maternal booster vaccine containing IPV compared with those born to mothers who did not receive the booster. This leaves some infants insufficiently protected against poliomyelitis until a pre-school booster is administered at 3 years and 4 months. These findings support a change in the UK schedule, to remove the IPV component from the maternal vaccine or add an IPV-containing booster in the second year of life. Abstract: Multivalent diphtheria, tetanus, acellular pertussis and inactivated poliovirus vaccine (DTaP/IPV) has been offered to pregnant women in the United Kingdom since 2012. To assess the impact of maternal DTaP/IPV immunisation on the infant immune response to IPV, we measured poliovirus-specific neutralising antibodies at 2, 5 and 13 months of age in a randomised, phase 4 study of Repevax or Boostrix/IPV in pregnancy and in a non-randomised group born to women not given DTaP/IPV in pregnancy. Infants whose mothers received DTaP/IPV were less likely to seroconvert after three IPV doses than those whose mothers did not receive DTaP/IPV. At 13 months of age, 63/110 (57.2 %), 46/108 (42.6 %) and 40/108 (37.0 %) were seropositive to types 1 to 3, compared with 20/22 (90.9 %), 20/22 (90.9 %) and 14/20 (70.0 %) (p-values 0.003, <0.001 and 0.012). UK infants whose mothers are given DTaP/IPV in pregnancy may be insufficiently protected against poliomyelitis until their pre-school booster.